The Clinical Effects of Synsepalum dulcificum: A Review - Suwaibah, Abd Hadi; Kaki B., Swarny; Muniandy, Sekaran; Malilikarjuna, Rao Pichik (2014)
Synsepalum dulcificum or the “miracle fruit” is well known for its taste-modifying ability. The aim of this review was to assess the published medically beneficial as well as potential characteristics of this fruit. A search in three databases, including PubMed, ScienceDirect, and Google Scholar, was made with appropriate keywords. The resulting articles were screened in different stages based on the title, abstract, and content. A total of nine articles were included in this review. This review summarized the findings of previously published studies on the effects of miracle fruit. The main studied characteristic of the fruit was its effect on the taste receptors, resulting in the sweet sensation when substances with acidic content were ingested. This effect was shown to be related to a glycoprotein called “miraculin.” Other beneficial characteristics of this fruit were its antioxidant and anticancer abilities that are due to the various amides existing in the miracle fruit. Apart from the above, the other observed effect of this fruit was its antidiabetic effect that was tested in rats. Further studies should be conducted to establish the findings. The miracle fruit can be a healthy additive due to its unique characteristics, including sour taste sensation modification as well as its antioxidant and antidiabetic effects.